Multiple presentation of mitochondrial disorders. Issue 3 (1st September 1999) - Nissenkorn, Andreea; Zeharia, Avraham; Lev, Dorit; Fatal-Valevski, Aviva; Barash, Varda; Gutman, Alisa; Harel, Shaul; Lerman-Sagie, Tally
Abstract : The aim of this study was to assess the heterogeneous clinical presentations of children with mitochondrial disorders evaluated at a metabolic neurogenetic clinic. The charts of 36 children with highly suspected mitochondrial disorders were reviewed. Thirty one children were diagnosed as having a mitochondrial disorder, based on a suggestive clinical presentation and at least one of the accepted laboratory criteria; however, in five children with no laboratory criteria the diagnosis remained probable. All of the patients had nervous system involvement. Twenty seven patients also had dysfunction of other systems: sensory organs in 15 patients, cardiovascular system in five, gastrointestinal system in 20, urinary system in four, haematopoietic system in four, and endocrine system in nine. The clinical presentation was compatible with an established syndrome in only 15 children. Severe lactic acidosis or ragged red muscle fibres were encountered in very few patients. These results suggest that mitochondrial disorders should be evaluated in children presenting with a complex neurological picture or multisystem involvement.